2021
DOI: 10.1007/s00044-021-02704-x
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine receptors as promising targets for the management of ocular diseases

Abstract: The ocular drug discovery arena has undergone a significant improvement in the last few years culminating in the FDA approvals of 8 new drugs. However, despite a large number of drugs, generics, and combination products available, it remains an urgent need to find breakthrough strategies and therapies for tackling ocular diseases. Targeting the adenosinergic system may represent an innovative strategy for discovering new ocular therapeutics. This review focused on the recent advance in the field and described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 124 publications
0
13
0
Order By: Relevance
“…On the negative side of adenosine-mediated inflammation suppression, many solid tumors escape immune response by increasing the concentration of adenosine in the tumor microenvironment. Both animal studies and clinical trials have shown that blocking A 2A AR can induce tumor regression (Sun et al, 2022).…”
Section: A 2a Ar Allosteric Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the negative side of adenosine-mediated inflammation suppression, many solid tumors escape immune response by increasing the concentration of adenosine in the tumor microenvironment. Both animal studies and clinical trials have shown that blocking A 2A AR can induce tumor regression (Sun et al, 2022).…”
Section: A 2a Ar Allosteric Modulatorsmentioning
confidence: 99%
“…In addition to the several physiological effects of adenosine, its receptor-mediated signaling has many documented effects on the progression of countless pathological states ( Karmouty-Quintana et al, 2013 ). Among the main ones, modulation of adenosine receptors has been indicated as a promising therapeutic strategy in pathological states such as cancer ( Vijayan et al, 2017 ; Allard et al, 2020 ), cardiovascular diseases ( Reiss et al, 2019 ), pain ( Vincenzi et al, 2020a ), neurological/neurodegenerative diseases ( Blum et al, 2018 ; Sebastião et al, 2018 ; Jenner et al, 2021 ; Merighi et al, 2021 ), neuropsychiatric disorders ( Pasquini et al, 2022 ), inflammatory diseases ( Pasquini et al, 2021 ; Antonioli et al, 2022 ), respiratory diseases ( Caruso et al, 2013 ), ocular diseases ( Spinozzi et al, 2021 ), diabetes, and other metabolic disorders ( Antonioli et al, 2015 ; Sanni and Terre’Blanche, 2021 ). Despite this encouraging profusion of experimental evidence, relatively few adenosinergic system-based drugs have so far achieved clinical approval.…”
Section: Introductionmentioning
confidence: 99%
“…Adenosine receptors are numerous in ocular tissue, such as the ciliary body, the trabecular meshwork, the sclera, and the retina (61). We identified nine clinical trials that evaluated compounds acting on an adenosine receptor, but to date none of the compounds have succeeded in progressing to FDA approval (62)(63)(64). A single phase I/IIA trials is currently underway [NCT04585100].…”
Section: Adenosine Receptor Agonistsmentioning
confidence: 99%
“…Approved therapeutics for treatment of ocular diseases include steroids such as hydrocortisone, triamcinolone acetonide, fluocinolone, and dexamethasone; antibiotics such as fluoroquinolones, tetracyclines, and aminoglycosides; and biological pharmaceuticals such as anti-VEGFs. Experimental therapeutics currently being investigated include antioxidants such as glutathione and ascorbic acid, complement factor inhibitors such as avacincaptad pegol and APL-2, and novel therapeutic mechanisms such as mesenchymal stem cell extracellular vesicles, miotic based eye drops, viral vectors for gene therapy, and adenosine receptors (13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%